Eksperimen Pembelajaran Matematika Melalui Strategi Pembelajaran Jigsaw Dan Group Investigation Terhadap Hasil Belajar Ditinjau Dari Motivasi Belajar Siswa Kelas Vii Semester Gasal MTs Negeri 1 Surakarta - Vironika, Novi Oktaviani, Drs. Slamet HW, M.Pd (2017)
ABSTRACT Novi Oktaviani Vironika / A410130134. EKSPERIMEN PEMBELAJARAN MATEMATIKA MELALUI STRATEGI PEMBELAJARAN JIGSAW DAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS VII SEMESTER GASAL MTs NEGERI 1 SURAKARTA. Skripsi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Desember 2016 This research aims to examined: (1) the influence of the learning method of Jigsaw and Group Investigation toward the result of mathematics learning, (2) the influence of students' learning motivation toward the result of mathematics learning, (3) the interaction between learning method and students' learning motivation toward the result of mathematics learning. Type of the research quantitative with quassi experimental design. The samples of the research are taken by using cluster random sampling. The sampling of the population of all students of grade VII odd semester of MTs Negeri 1 Surakarta academic year 2016/2017. The technique of collecting data is using quetionare, test, and documentation. Before analyzing the data, normality test and homogeneity test are test first. The technique of analyzing the data is using unbalanced two-way analysis of variance with α = 5%. The result of the research is gained: (1) there are influence of the learning method of Jigsaw and Group Investigation toward the result of mathematics learning, (2) there are influence of students' learning motivation toward the result of mathematics learning, (3) there is no interaction between learning method and students' leaning motivation toward the result of mathematics learning. Keyword: Jigsaw, Group Investigation, the result of mathematics learning, learning motivation